Productive waqf governance reform in the digital economy: A comparative legal study - Al Hanif, Azzam; Zahro’, Khurun’in; Aziz, M. Sallahudin Rifqi Kurnia; Rusli, Lathiefa; Syahruddin, Syahruddin (Journal of Islamic Law on Digital Economy and Business, 2026)
Purpose – This study examines and compares the legal and governance frameworks of productive waqf in Indonesia and selected Muslim jurisdictions, such as Malaysia, Turkey, and Saudi Arabia, to identify the structural determinants of waqf performance. It aims to provide policy-relevant insights for reforming Indonesia’s waqf law within the broader context of Islamic law, governance reform, and the digital economy. Methodology – This research employs doctrinal and comparative legal methodologies using qualitative analysis. Primary legal sources consist of statutes, regulations, and institutional guidelines governing waqf, while secondary sources include academic literature and official reports. A structured comparative framework was applied to assess regulatory coherence, institutional capacity, stewardship mechanisms, investment governance, and digital governance across jurisdictions. Findings – The findings reveal that jurisdictions with centralized legal authority and integrated digital governance systems demonstrate comparatively stronger accountability, higher institutional capacity, and more productive utilization of waqf assets. In contrast, Indonesia’s fragmented regulatory structure, uneven nazhir professionalism, conservative investment rules, and limited digital integration constrain productive waqf development. Implications – This study highlights the need for Indonesia to strengthen institutional coordination, standardize nazhir competency frameworks, expand Shariah-compliant investment instruments, and establish an integrated national digital waqf information system to enhance transparency, efficiency, and sustainability. Originality – This study contributes original insights by offering a systematic cross-jurisdictional legal comparison and proposing an Integrated Waqf Governance Model that incorporates regulatory governance, institutional capacity, stewardship, and digital governance as key determinants of productive waqf performance in the digital economy era.